Pengabaian Alat Bukti Petunjuk Oleh Hakim Sebagai Alasan Kasasi Penuntut Umum dan Pertimbangan Mahkamah Agung Memutus Perkara Penggelapan dalam Jabatan - Ganang Widyo Nindito (Sebelas Maret University, 2019)
This research aims are to fnd out the evidence tool guidance abandonment by the judge as a Cassation Prosecutor’s reason and Supreme Court’s consideration in deciding an embezzlement case in offce. This research is classifed in normative law research. Cases that examined in Supreme Court Ruling Number 1243K/Pid/2015 is an embezzlement case in offce done by Defendant Desi Nanda Sari. This case began when the defendant who worked as a cashier at ‘Gudang Timbangan Mandiri Boluk’ who owned by Ny. Normah Sembiring given the investment by Ny. Normah Sembiring amount to Rp. 155.000.000,00 (one hundred and ffty fve million rupiah) as an investment in paying for the palm fruit purchased from the society. Several months passing by, Defendant Desi Nanda Sari didn’t pay the investment and proft amount to Rp 52.000.000,00 (ffty two million rupiah) so that the victim feels aggrieved and reported the Defendant’s act on indictment Article 374 Criminal Code because of the defendant’s action who have committed embezzlement in offce and resulted in a loss. Based on research result and discussion resulting conclusion that The Defendants volunteered cassation with reason put forward is that the judge not carefully in adjudicate an evidence tool in the form of instructions as appropriate. The cassation of public prosecutor’s submission reason have been in accordance with Article 253 section (1) Criminal Procedural Code, with consideration that The Judge didn’t properly and correctly consider all the facts of the trials. This matter has been accordance with the provisions on Article 256 Jo Article 193 section (1) Criminal Procedural Code with the consideration that The Judge of The Simalungun Court has applied the law incorrectly by not paying attention to the evidence tool in the form of instructions in the trials, Supreme Court granted The Supplication of Cassation by The Public Prosecutor and created a new law.Keywords: Evidence Tool, Cassation, Embezzlement in Offce.